Respuesta :
Answer:
Step-by-step explanation:
3y = -x + 6
y = -1/3x + 2
y - 3 = -1/3(x + 1)
y - 9/3 = -1/3x - 1/3
y = -1/3x + 8/3
Answer:
x - 8 = -3y
Step-by-step explanation:
x + 3y = 6
Convert to y = mx + b form, and we get: x - 6 = -3y
Remember m is our slope, and in this case, it is simply one.
Because the line we're solving for is parallel, it must have the same slope.
y = 1x + b, we just have to solve for b now.
This is done by plugging in our points, which looks like: -1 + b = -3 x 3
simplify: -1 + b = -9, b = -8
Combining what we know yields: x - 8 = -3y
Hope this helps :)